2015
DOI: 10.1007/s00220-015-2487-5
|View full text |Cite
|
Sign up to set email alerts
|

Painlevé Representation of Tracy–Widom $${_\beta}$$ β Distribution for $${\beta}$$ β = 6

Abstract: In [36], we found explicit Lax pairs for the soft edge of beta ensembles with even integer values of β. Using this general result, the case β = 6 is further considered here. This is the smallest even β, when the corresponding Lax pair and its relation to Painlevé II (PII) have not been known before, unlike cases β = 2 and 4. It turns out that again everything can be expressed in terms of the Hastings-McLeod solution of PII. In particular, a second order nonlinear ordinary differential equation (ODE) for the lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 55 publications
1
28
0
3
Order By: Relevance
“…Its cumulative distribution, F β = Prob[χ β ≤ x], is known as the β-Tracy-Widom (TW) distribution. For β = 1, 2, 4, F β can be written explicitly in terms of a special solution of a Painlevé equation [8,9] and for β = 6 in terms of an additional Painlevé transcendent [179,180]. For other values of β, it can be shown that F β describes the fluctuations of the ground state of a one-dimensional random Schrödinger operator, called the "stochastic Airy operator" [181,182].…”
Section: Extreme Statistics In Random Matrix Theorymentioning
confidence: 99%
“…Its cumulative distribution, F β = Prob[χ β ≤ x], is known as the β-Tracy-Widom (TW) distribution. For β = 1, 2, 4, F β can be written explicitly in terms of a special solution of a Painlevé equation [8,9] and for β = 6 in terms of an additional Painlevé transcendent [179,180]. For other values of β, it can be shown that F β describes the fluctuations of the ground state of a one-dimensional random Schrödinger operator, called the "stochastic Airy operator" [181,182].…”
Section: Extreme Statistics In Random Matrix Theorymentioning
confidence: 99%
“…During the last decade, there were written quite a lot of works on relations of the equations of IDM for Painlevé type ODEs with evolution linear equations of quantum mechanics and, starting from work [36], of quantum field theory [1]- [3], [7], [8], [14]- [17], [19]- [24], [26], [27], [32], [35]- [38], [41], [43]- [45].…”
Section: Introductionmentioning
confidence: 99%
“…That same paper provides new proofs of the β = 2, 4 spiked soft edge laws using the analog of the PDE (1.12) derived in [3]. It is further worth mentioning that more recently Rumanov [23] has found a Painlevé II formula at the β = 6 soft edge (the first known outside β = 1, 2, 4) once more using the spiked/PDE picture of [3].…”
Section: Riccati Correspondence and Pdesmentioning
confidence: 77%
“…In brief, the introduction of the variable boundary condition produces the previously missing space-like variable in the corresponding PDE(s). These PDEs have subsequently been used to confirm a conjectured Painlevé formula for the spiked β = 4 TracyWidom law form [31], and more recently has led to Painlevé formulas at β = 6 [23] (the first appearance of such outside of β = 1, 2, 4).…”
Section: Riccati Correspondence and Pdesmentioning
confidence: 94%
See 1 more Smart Citation